The right call - Greenwald, Tommy, 1962- (Game changer, 2025)
"Cal Klondike's life revolves around baseball. He's the Walthorne Baseball Academy's star pitcher, and everyone from his coach to his dad to the town sports blogger is telling Cal he has an unlimited future in the sport. But with all this attention comes a lot of added stress, especially as the season kicks into high gear and college and pro scouts start to show up at the games. Inevitably, tensions that have been bubbling under the surface finally boil over, culminating in a confrontation that could change Cal's relationship to baseball forever."-- Page [2] of cover.